Leitura em inglês com surdos: possibilidades - Lopes, José Carlos Barbosa (2009)
This research aims at discussing reading in English with deaf people in Applied Linguistics in the Education and Language area. It is, specifically, involved with the group Language, Creativity and Multiplicity (LCM), a subdivision of the projects developed by the Research Group Language in Activities in School Contexts (LACE) from Catholic University of São Paulo, SP. This study investigated the reading in English process within interactions with a group of deaf adolescents in six classes, developed in an eastern city in São Paulo. It is theoretically based on researchers (Souza, 1998; Lodi, 2004; Goldfeld, 2002; Campello, 2008) who discuss the essential visual approach of Libras connected to an enunciative-discursive perspective by Bakhtin / Volochinov (1929 / 2006). In this regard, the research sought to emphasize the verbal-visual (Brait, 2008) realization of texts and Libras in the production of sense and meanings in order to move the creative knowledge formulation (Liberali, 2006a, b). The analysis rests on types of questions (Lucioli, 2003) and answers (Pontecorvo, 2005; Orsolini, 2005) raised in texts discussions, which provide new ways to transform human activity and resources required for a qualitative leap in development (Vygotsky 1934/2005; Leontiev, 1977). This is a critical collaborative intervention research (Pennycook, 2006; Magalhães, 2006f; Liberali, 2009), which emphasizes individuals interaction in activities mediated by language in use, searching for alternatives to knowledge production in the social world. The data show, therefore, deaf students possibility of participation in the context of reading in English focused. However, it is necessary to direct attention to more deepening discursive practices in the interactive process, so that the multiplicity of senses promote the production of new knowledge